Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.6 - Factoring Trinomials - Exercise Set: 17

Answer

$(x-4)(2x-3)$

Work Step by Step

The two numbers whose product is $ac= 2(12)=24 $ and whose sum is $b= -11 $ are $\{ -8,-3 \}$. Using these two numbers to decompose the middle term, then the factored form of the given expression, $ 2x^2-11x+12 $,is \begin{array}{l}\require{cancel} 2x^2-8x-3x+12 \\\\= (2x^2-8x)-(3x-12) \\\\= 2x(x-4)-3(x-4) \\\\= (x-4)(2x-3) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.